Occurrence and evolutionary inferences about Kranz anatomy in Cyperaceae (Poales) - Martins, Shirley; Alves, Marccus; Scatena, Vera L. [UNESP] (FapUNIFESP (SciELO), 2015)
Cyperaceae is an angiosperm family with the greatest diversity of species with Kranz anatomy. Four different types of Kranz anatomy (chlorocyperoid, eleocharoid, fimbristyloid and rhynchosporoid) have been described for this angiosperm family, and the occurrence and structural characteristics of these types are important to trace evolutionary hypotheses. The purpose of this study was to examine the available data on Cyperaceae Kranz anatomy, emphasizing taxonomy, geographic distribution, habitat and anatomy, to infer the potential origin of the Kranz anatomy in this family. The results showed that the four types of Kranz anatomy (associated with C4 photosynthesis) in Cyperaceae emerged numerous times in unrelated phylogenetic groups. However, the convergence of these anatomical types, except rhynchosporoid, was observed in certain groups. Thus, the diverse origin of these species might result from different environmental pressures that promote photorespiration. Greater variation in occurrence of Kranz anatomy and anatomical types was observed in Eleocharis, whose emergence of the C4 pathway was recent compared with other genera in the family, and the species of this genus are located in aquatic environments.
Keywords: Anatomy; Cyperaceae; Phylogeny; Taxonomy; Ultrastructure